Bilateral Ocular Affection Associated with Trypanosoma evansi Infection in German Shepherd Dog: A Case Report - Kumar Gupta, Kapil; Gupta, Neha; Punia, Sunil; Dutta, Nishchal; Sudan, Vikrant (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Trypanosomosis, an arthropod-borne infectious disease caused by a flagellate protozoan parasite, Trypanosoma evansi, poses significant economic challenges, particularly in the tropical regions such as India (Jaiswal et al., 2015). The disease affects bovines, canines, felines, and camelids. It is primarily transmitted mechanically by the biting haematophagous flies, with outbreaks becoming more frequent during the rainy season due to increased vector population (Jaiswal et al., 2015). Initially restricted to wild animals, over the time, disease has spread to the domestic animals (Sudan et al., 2017). Clinically, trypanosomosis presents with symptoms such as anorexia, emaciation, intermittent fever, progressive anaemia, conjunctivitis, limb edema, and superficial lymphadenopathy (Pandey et al., 2015). Neurological manifestations, like delirium, head pressing, ataxia, rear limb paralysis, and tonic-clonic seizures, have also been reported (Jaiswal et al., 2015; Sudan et al., 2017). Ocular involvement in canine trypanosomosis is rare, with limited literature available on the subject (Behera et al., 2017; Abbas et al., 2021). During disease development the parasites travel down from brain through optic nerve and causes deposition of immune complex in aquas humour which clinically results into development of corneal edema and opacity (Reddy and Sivajothi, 2017). This case report presents a clinical case of T. evansi induced ocular manifestations in a German Shepherd dog and its therapeutic management with diminazene aceturate in conjunction with supportive therapy.